KONSTRIBUSI PAJAK KENDARAAN BERMOTOR DAN PAJAK BEA BALIK NAMA KENDARAAN BERMOTOR PADA PENDAPATAN ASLI DAERAH - Purnamawati, Evi (Solusi, 2021)
Regional original income is an indicator of regional independence in terms of finance. The greater the revenue and the percentage of original regional revenue (PAD) to the total regional revenue, the more independent the region is. The formulation of the problem whether the contribution of Motor Vehicle Tax (PKB) and Motor Vehicle Title Fee Tax (BBNKB) has an effect on Regional Original Income (PAD). Motorized Vehicle Tax (PKB) and Motor Vehicle Transfer Fee Tax (BBNKB) have a significant effect on Regional Original Income (PAD). Local taxes are an important source of regional income to finance development and regional governance. Regional tax policies are based on the principles of democracy, equity and justice, community participation and accountability with due regard to regional potential. With the enactment of regional regulations relating to taxes, the ability of regions to finance their expenditure needs will increase, because regions can easily adjust their income. The government is expected to be able to maintain and make more efforts to increase Motor Vehicle Tax revenue, it is necessary to have firm sanctions and improve the existing administrative system.